Multiproxy synthesis at the Arlington Archosaur Site: New insights into Cretaceous paralic paleoenvironments and regional stratigraphy, Woodbine Group, Texas, USA - Christopher R. Noto; Peter P. Flaig; Maria Antonietta Lorente (Sedimentologika)
Ecosystems of the 'mid' Cretaceous are significant but poorly understood, due in large part to a sparse fossil record. Existing fossils, particularly in North America, are not chronostratigraphically well-constrained, further hampering comparisons of species and ecosystems across Laramidia and Appalachia. Efforts to overcome this lack of temporal resolution typically involve systematic collection of ashfall deposits, geochemistry, and biostratigraphy. Here we describe a new, high-resolution palynological and sedimentologic dataset from the Arlington Archosaur Site (AAS) of the Lewisville Formation (Woodbine Group; Middle Cenomanian). The integration of these new data with existing biostratigraphic, macrofossil (vertebrate, invertebrate, botanical), lithologic, ichnologic, and geochemical data allows for a comprehensive paleoenvironmental reconstruction and assessment of paleoenvironmental evolution during AAS deposition. Depositional environments are paralic and include nearshore, shallow-marine tidal-flat, lagoonal, tidal-delta deposits, fluvial-distributary channels, and associated floodplain environments including wetlands (swamp-marsh-lakes) and paleosols. The presence of the Cyclonephelium compactum – C. membraniphorum (Ccm) morphological plexus throughout the AAS deposit suggests a younger minimum age of (early) late Cenomanian for deposits, indicating possible southward expansion of this group into the Cretaceous Western Interior Seaway (CWIS) coincident with the onset of the Plenus Cold Event (PCE) of OAE2. The revised age estimate for the AAS suggests that Woodbine deposition at more proximal clastic source areas continued into the late Cenomanian, coeval with down dip Eagle Ford Group sedimentation. This study has important implications for the biogeography of western Appalachia and the response of terrestrial and shallow marine ecosystems of the southeastern CWIS to the onset of OAE2.